Antidiabetic Flavonoids from Fruits of Morus alba Promoting Insulin-Stimulated Glucose Uptake via Akt and AMP-Activated Protein Kinase Activation in 3T3-L1 Adipocytes - Sung Ho Lim; Jae Sik Yu; Ho Seon Lee; Chang-Ik Choi; Ki Hyun Kim (MDPI AG, 2021)
Morus alba (Moraceae), known as white mulberry, has been used to treat fever, protect against liver damage, improve eyesight, and lower blood sugar levels in traditional oriental medicine. Few studies have been conducted on the antidiabetic compounds identified from M. alba and their underlying mechanisms of action. Consequently, in this study, the fruits of M. alba were investigated for potential antidiabetic natural products using 3T3-L1 adipocytes. Phytochemical analysis of the ethanolic extract of M. alba fruits, followed by high-performance liquid chromatography (HPLC), purification led to the isolation of two main compounds: rutin and quercetin-3-O-β-d-glucoside (Q3G). Long-term use of available drugs for treating type 2 diabetes ((T2D) is often accompanied by undesirable side effects, which have generated increased interest in the development of more effective and safer antidiabetic agents. Examination of the isolated compounds, rutin and Q3G, for antidiabetic or anti-obesity properties or both in 3T3-L1 adipocytes demonstrated that they both improved glucose uptake via Akt-mediated insulin signaling pathway or AMP-activated protein kinase (AMPK) activation in 3T3-L1 adipocytes. The compounds also showed a positive effect on lipid accumulation in adipocytes, suggesting that glucose uptake occurred through activation of the Akt and AMPK signaling pathway without inducing adipogenesis. Taken together, our findings suggest that rutin and Q3G in M. alba fruits have the potential to induce fewer side effects such as weight gain, and these active compounds could be potential therapeutic candidates for the management of T2D.